Straw interference in the emergence of talquezal seeds from different origins - Marchi,Sidnei R. (2020)
Abstract Background: Talquezal (Paspalum virgatum L.) has become one of the main pasture weeds due to its association with the Urochloa brizantha death syndrome, a disease that causes the progressive death of clumps of susceptible grasses in patches, which leads to weed colonization and pasture degradation. Understanding the weed emergence pattern is essential in decision making for management strategies. Objective: Thus, this study aimed to evaluate the emergence pattern of talquezal seedlings according to its origin and the amount of straw covering the soil. Methods: The experiment was carried out in a greenhouse in a completely randomized design, with six replications and treatments arranged in an 8 × 3 factorial scheme with eight amounts of Urochloa brizantha straw covering the seeds (0, 0.5, 1.0, 2.0, 4.0, 6.0, 8.0, and 10.0 ton ha-1) and three collection sites (Rondonópolis, Redenção, and Cacoal). The effect of the origin and amount of straw was evaluated by the percentage of emergence, relative emergence frequency, mean emergence time, emergence synchrony, and emergence speed index of seedlings obtained over 35 days after sowing. Results: Talquezal seeds showed high seedling emergence vigor regardless of their origin under amounts of straw lower than 4.0 ton ha-1. Conclusions: The result suggests that the amounts of U. brizantha straw higher than 4.0 ton ha-1 on the soil surface, the lower is the percentage of Talquezal seedling emergence.